2018
DOI: 10.1111/jav.01717
|View full text |Cite
|
Sign up to set email alerts
|

Behavioural plasticity under a changing climate; how an experimental local climate affects the nest construction of the zebra finchTaeniopygia guttata

Abstract: Successful reproduction in most avian species is dependent on the construction of a nest that provides protection and a suitable microclimate for the eggs and developing nestlings. Observational studies suggest that climatic variation may affect the structure of the nest, but to date there have been no attempts to experimentally determine the role that local climate plays in the construction of a suitable nest. Using a within‐individual counter balanced design we investigated how nest composition and construct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 28 publications
2
14
0
Order By: Relevance
“…Similar nest modifications were also reported by a study that measured the nests produced by the pairs in this same experiment, showing a 20% nest mass reduction in the 30 °C treatment (Campbell et al . 2018). These results suggest that the concurrent contribution of behavioural adjustments in incubation pattern and nest‐building can prevent overheating and help in buffering clutches from the influence of environmental temperature.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar nest modifications were also reported by a study that measured the nests produced by the pairs in this same experiment, showing a 20% nest mass reduction in the 30 °C treatment (Campbell et al . 2018). These results suggest that the concurrent contribution of behavioural adjustments in incubation pattern and nest‐building can prevent overheating and help in buffering clutches from the influence of environmental temperature.…”
Section: Discussionmentioning
confidence: 99%
“…This first attempt was interrupted on day 9 of incubation, when nests were removed for another study looking at temperature‐dependent variation in nest size and building material (Campbell et al . 2018). At this point, new rattan nesting baskets and material were provided and birds were allowed a second attempt where they could rebuild their nest, lay and incubate a new clutch, and raise a brood of chicks to independence.…”
Section: Methodsmentioning
confidence: 99%
“…In general, nests built in cold conditions have better thermal insulation (Deeming et al, 2012), for example, at the beginning of the breeding season in temperate habitats (Mainwaring & Hartley, 2008), at high latitudes (Mainwaring et al, 2012(Mainwaring et al, , 2014, or at high altitudes (Heenan et al, 2015; but also see Schöll & Hille, 2014). There is, indeed, experimental evidence showing that birds can plastically adjust nest composition in response to shifting environmental conditions (Campbell et al, 2018), which is also supported by correlative studies (Deeming et al, 2012;McGowan et al, 2004).…”
mentioning
confidence: 86%
“…Flexibility in response to temperature in nest building has been demonstrated experimentally in captive zebra finches (Taeniopygia guttata). Zebra finches that were housed at 18°C built heavier nests than when they were housed at 30°C (Campbell et al 2018), irrespective of the order in which they experienced the two temperatures. The authors concluded that birds built heavier nests in the cooler temperature in an attempt to retain heat within the nest, which would in turn aid reproductive success.…”
Section: Introductionmentioning
confidence: 92%
“…In this study, we therefore investigated the relationship between individual flexibility in nest morphology and reproductive success. Based on the Campbell et al (2018) experiment we expected birds to build bigger nests in cooler than in warmer ambient temperatures. Our experiments, however, differed in two key ways.…”
Section: Introductionmentioning
confidence: 99%